Developing Listening Skills for Tertiary Level Learners - Alam, Zerin (Dhaka University Journal of Linguistics, 2010)
Although ELT in Bangladesh is moving away from the traditional grammar translation approach towards a CLT framework, we still do not give emphasis to all four skills which is recommended in the communicative approach. As listening remains a neglected skill the writers argue for the need to incorporate this skill at the tertiary level in order to improve communicative competence and in particular proficiency in Academic English. The article first discusses the theoretical overview for teaching listening including listening for academic purposes. Then it presents practical and effective tasks and materials that are appropriate for the Bangladeshi university context and will develop students' proficiency in Academic English. DOI: 10.3329/dujl.v2i3.4141 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 19-52